Factors influencing the adoption of bundled sustainable agricultural practices: a systematic literature review - Rajendran, Natasha; Tey, Yeong Sheng; Brindal, Mark Kennion; Ahmad Sidique, Shaufique Fahmi; Shamsudin, Mad Nasir; Radam, Alias; Abdul Hadi, Ahmad Hanis Izani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Farm sustainability issues are diverse but interconnected and complex. Many organizations have begun to promote packaged sustainable agricultural practices (SAPs). Some of these bundled SAPs (i.e. organic agriculture and integrated pest management) have long been employed by farmers, and studied by scientists seeking to understand their response to these alternative agricultural approaches. This paper reviews and synthesizes recent research in this area. It identifies key explanatory factors, which frequently lead to the adoption of bundled SAPs. Vote count analysis reveals that variables implying economic motivation and facilitation regularly explain farmers' behaviour. In addition, a new finding emerged, in which factors inferring higher learning and superior management capacity provided further indicators to adoption. In particular, the training that provided by non-governmental organizations and rural institutions complements change agents (i.e. public extension services). While this finding is novel, more research is required to generate better understanding of farmer reaction to bundled SAPs, particularly dynamic ones (i.e. private standards) in which farm business sustainability depends upon good agricultural practices being implemented.